Effects of Salt Field Waste-Generated Bio-Organic Fertilizer Application on Bacterial Community Structure in Tea Plantations Rhizosphere Soil - Chengran Yu; Liuting Zhou; Xiaoyun Huang; Xiaofeng You; Jiali Lin; Haidong Han; Xiusheng Huang (Agronomy)
This study aims to investigate the impact of salt field waste-generated bio-organic fertilizer application on the bacterial community structure within the rhizosphere soil of tea plants. After the administration of salt field waste-generated bio-organic fertilizer, the content of tea polyphenols in tea decreased, while the content of caffeine and free amino acids increased. The results showed that the dominant bacterial species in the rhizosphere soil of tea plants were Chloroflexi, Acidobacteriota, and Proteobacteria. The most dominant genus were k__Bacteria__p__Proteobacteria__c__uncultured__o__uncultured__f__uncultured__g__uncultured, k__Bacteria__p__Acidobacteriota__c__Acidobacteriae__o__Subgroup_2__f__Subgroup_2__g__Subgroup_2, k__Bacteria__p__Chloroflexi__c__AD3__o__AD3__f__AD3__g__AD3, k__Bacteria__p__Chloroflexi__c__Ktedonobacteria__o__Ktedonobacterales__f__Ktedonobacteraceae__g__HSB_OF53-F07, and g__Acidothermus. Following the application of bio-organic fertilizer, g__AD3, g__Subgroup_2, and g__HSB_OF53_F07 in the rhizosphere soil of the tea plants exhibited a decreasing trend compared to the control group. p_Proteobacteria was significantly increased, and p_Chloroflexi was considerably decreased in soils treated with bioorganic fertilizers, indicating that bio-organic fertilizers might influence the soil microbial structure in the rhizosphere soil of tea plants. Network association analyses showed a strong positive correlation between g_Candidatus_Solibacter and g_Bryobacter and a significant negative correlation between g_AD3 and g_ADurb.Bin063_1. Applying salt field waste-generated bio-organic fertilizers might effectively adjust the bacterial community structure in tea plants’ rhizosphere soil, improving the quality of tea. This study provides valuable insights into the potential benefits of utilizing bio-organic fertilizer from salt field waste in tea plantations.